2020
DOI: 10.3390/ijms21207777
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Factor BDNF, Physiological Functions and Therapeutic Potential in Depression, Neurodegeneration and Brain Cancer

Abstract: Brain-derived neurotrophic factor (BDNF) is one of the most distributed and extensively studied neurotrophins in the mammalian brain. BDNF signals through the tropomycin receptor kinase B (TrkB) and the low affinity p75 neurotrophin receptor (p75NTR). BDNF plays an important role in proper growth, development, and plasticity of glutamatergic and GABAergic synapses and through modulation of neuronal differentiation, it influences serotonergic and dopaminergic neurotransmission. BDNF acts as paracrine and autocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
320
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(335 citation statements)
references
References 261 publications
(309 reference statements)
10
320
0
5
Order By: Relevance
“…Some studies have found myokines, such as brain-derived neurotrophic factor and irisin, through specific signaling pathways to mediate depression symptoms. 9 , 41 Finally, low handgrip strength influences depression through psychosocial mechanisms. Older adults with low handgrip strength usually experience a decline in physical ability and function, which limits their opportunities to participate in outdoor activities, decreasing possible social contact with other people.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found myokines, such as brain-derived neurotrophic factor and irisin, through specific signaling pathways to mediate depression symptoms. 9 , 41 Finally, low handgrip strength influences depression through psychosocial mechanisms. Older adults with low handgrip strength usually experience a decline in physical ability and function, which limits their opportunities to participate in outdoor activities, decreasing possible social contact with other people.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF interacts with tropomyosin-related kinase B (TrkB) and p75 cellular receptors and supports maintenance of normal brain function, neurite outgrowth and synaptic plasticity [ 73 , 74 ]. Several lines of evidence indicate BDNF levels play an important role in the pathogenesis of several neurodegenerative diseases, including Alzheimer’s disease (AD) [ 75 ]. In the brain of AD patients or aged subjects, BDNF expression levels are lower compared with healthy subjects [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of Parkinson’s disease (PD), BDNF enhances the survival of dopaminergic neurons, improves dopaminergic neurotransmission and motor performance [ 86 ]. Moreover, as previously underlined, neurotrophins prevent cell death and support neuronal proliferation and maturation enhancing both growth and function of affected neurons in Alzheimer’s disease (AD) and PD [ 75 , 86 , 87 ]. Despite the under threshold of BDNF z -score value derived by IPA, both transcript and protein expression analysis by PCR and WB confirmed a significant increase of the neurotrophic factor expression in SH-SY5Y cells treated with the hill extract.…”
Section: Discussionmentioning
confidence: 99%
“…As reported above, both cross-sectional and longitudinal studies have indicated that administration of antidepressants and mood stabilizers such as lithium and valproate has normalized BDNF, promoting so, a neuroprotection stress-induced, protecting the cells through anti-apoptotic pathways activation (Colucci-D’Amato et al, 2020 ). It can also increase the gray matter promoting neurogenesis in the subventricular zone of the lateral ventricle and subgranular zone of the hippocampal dentate gyrus, and improve cognitive functions such as learning and memory, both in animal and human studies (Sassi et al, 2002 ; Gould, 2007 ; Kempton et al, 2008 ; Machado-Vieira et al, 2009 ; Hashimoto, 2010 ; Corena-McLeod et al, 2013 ; Yu and Greenberg, 2016 ).…”
Section: Biomarkers Related To Neuroinflammation In Bipolar Disordermentioning
confidence: 94%